2006
DOI: 10.1152/japplphysiol.00562.2005
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive pro- and anti-inflammatory cytokine and growth factor response to exercise in leukocytes

Abstract: Leukocytosis following exercise is a well-described phenomenon of stress/inflammatory activation in healthy humans. We hypothesized that, despite this increase in circulating inflammatory cells, exercise would paradoxically induce expression of both pro- and anti-inflammatory cytokines and growth factors within these cells. To test this hypothesis, 11 healthy adult men, 18-30 yr old, performed a 30-min bout of heavy cycling exercise; blood sampling was at baseline, end-exercise, and 60 min into recovery. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
105
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 56 publications
14
105
0
3
Order By: Relevance
“…Therefore, it seems plausible that CD14 ϩ CD16 ϩ monocytes are responding to mild endotoxemia accompanying strenuous exercise (9,50) or EHS (68). A common finding when examining intracellular cytokine profiles with exercise, with or without hyperthermia, has been either no change or a slight reduction in the level of spontaneous TNF-␣ in cytokine-positive peripheral blood monocytes in trained (74,77,89) and untrained subjects (84), similar to the present study's responses in CD14 ϩϩ CD16 Ϫ monocytes. By contrast, Rhind et al (58) found corresponding increases in intracellular monocytic expression and circulating TNF-␣ during exhaustive exercise and subsequent cold exposure, changes that were suggested to be reflective of the inflammatory status of the cells before the exposure, or perhaps specific immune modulating influences accompanying exercise (58).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, it seems plausible that CD14 ϩ CD16 ϩ monocytes are responding to mild endotoxemia accompanying strenuous exercise (9,50) or EHS (68). A common finding when examining intracellular cytokine profiles with exercise, with or without hyperthermia, has been either no change or a slight reduction in the level of spontaneous TNF-␣ in cytokine-positive peripheral blood monocytes in trained (74,77,89) and untrained subjects (84), similar to the present study's responses in CD14 ϩϩ CD16 Ϫ monocytes. By contrast, Rhind et al (58) found corresponding increases in intracellular monocytic expression and circulating TNF-␣ during exhaustive exercise and subsequent cold exposure, changes that were suggested to be reflective of the inflammatory status of the cells before the exposure, or perhaps specific immune modulating influences accompanying exercise (58).…”
Section: Discussionsupporting
confidence: 80%
“…Early studies examining intracellular cytokine production have suggested that peripheral monocytes may not be a primary source of inflammatory cytokines released during strenuous exercise, despite well-documented increases in circulating TNF-␣ (74,77). This conclusion is also supported by more recent findings by Zaldivar et al (89) and Vassilakopoulous et al (84) suggesting that monocytes do not contribute significantly to augmented cytokine production following cycling exercise (30 -45 min, 75-80% V O 2peak ). Importantly, however, previous studies failed to distinguish between specific monocyte subsets, employing only single-color staining with CD14 ϩ (58, 84), CD33 ϩ (74 -77), or CD4 Dim (89) for monocyte identification, all of which are specific for the classic monocyte subset (5,12).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Most investigations have focused on macrophage or monocyte cell lines and demonstrated that catecholamines like epinephrine inhibit cellular production of TNF-α (e.g., [36]). Using intracellular fluorescent staining and flow cytometry, we found that the numbers of t-cells positive for TNF-α increased following exercise, but not the mean fluorescent intensity [6]. Goebel and coworkers [37] using stimulated whole blood obtained from human participants after exercise and other psychological stressors showed that TNF-α production increased only with exercise but was blunted by isoproterenol infusion.…”
Section: Discussionmentioning
confidence: 80%
“…Circulating t-cell numbers and function are influenced by brief periods of exercise [6,7], and a number of mechanisms have been proposed to explain these effects. First, as noted, exercise alters circulating factors and mediators (e.g., lactate, IL-6, catecholamines, growth hormone) that can affect t-cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%